Human capital transfer of German-speaking migrants in Eastern Europe, 1780s-1820s - Matthias Blum; Karl-Peter Krauss; Dmytro Myeshkov (Queen's University Centre for Economic History (QUCEH), 2021)
Prior to the Age of Mass Migration, Germans left central Europe to settle primarily in modernday Hungary, Serbia, Romania, Ukraine and Russia. Despite the harsh conditions that the first generation of settlers had to endure, their descendants often fared better, not worse, compared to native population groups. This study offers a possible explanation for this surprising outcome. We use data on approximately 11,500 individuals to estimate and compare basic numeracy scores of German settlers and other populations groups in target regions. We find that German settlers generally had superior basic numeracy levels, suggesting that these settlers must have contributed positively to the human capital endowment in their target regions. The numeracy of Germans was somewhat higher than the numeracy of Hungarians and substantially higher than the numeracy of Russians, Ukrainians and Serbs. We do not find noteworthy differences in terms of numeracy between German emigrants and the population they left behind, suggesting the absence of substantial migrant selection.
Keywords: N13; N23; 330; Migration; Economic History; Germany; Hungary; Russian Empire; Ukraine; Eastern Europe